Targeted phototherapy - Zonun Sanga (Termedia Publishing House, 2015)
Conventional phototherapy uses a whole body cabinet or body part machines for the hand, foot or scalp. It has many disadvantages, due to which new phototherapy techniques have been developed. These new techniques are called targeted phototherapy. They include excimer laser, the intense pulse light (IPL) system, photodynamic therapy, and an ultraviolet (UV) light source with a sophisticated delivery system which is easy to operate by hand. The mechanisms of action of targeted phototherapy systems are similar to those in conventional UVB/UVA therapy. They have many advantages including lower risk of side effects, avoidance of exposure of unnecessary sites, faster response, and shorter duration of treatment. But they also have disadvantages such as high costs and inability to use them for extensive areas. This review article discusses targeted phototherapy, its mechanisms of action, and advantages and disadvantages in comparison to conventional phototherapy.